Contabilidade aplicada à gestão de cooperativas na cidade de Araguaína: registro de relatos. - Meneses, João Marcos Sousa (Universidade Federal do Tocantins, 2023)
The present work is a study on the level of understanding of the cooperative managers in the city of Araguaína-TO about the accounting norm’s substance for cooperative societies, General Technical Interpretation (GTI) 2004. The data collection used was through a structured questionnaire, applied to three distinct managers in September of 2019. In order to analyze and describe the data collected, the theoretical contextualization was used. It is a field research, with exploratory study, of a documentary character and qualitative, descriptive approach. The results show that managers have little knowledge about the accounting norm and its application in the management of these ventures. Eventually, there is a need for greater commitment by the part of entities such like the Organization of Brazilian Cooperatives (OBC) it’s from Regional Accounting Council (RAC) to promote courses and events that can provide learning and professionalization on the accounting aspects of organizations cooperatives.